Expression and clinical significance of MAGE and NY‐ESO‐1 cancer‐testis antigens in adenoid cystic carcinoma of the head and neck. Issue 7 (13th February 2016) - Veit, Johannes A.; Heine, Daniela; Thierauf, Julia; Lennerz, Jochen; Shetty, Subasch; Schuler, Patrick J.; Whiteside, Theresa; Beutner, Dirk; Meyer, Moritz; Grünewald, Inga; Ritter, Gerd; Gnjatic, Sacha; et al.
Abstract: Background: Adenoid cystic carcinoma (ACC) of the head and neck is a rare but highly malignant tumor. Cancer‐testis antigens (CTAs) represent an immunogenic family of cancer‐specific proteins and thus represent an attractive target for immunotherapy. Methods: Eighty‐four cases of ACC were identified, the CTAs pan‐Melanoma antigen (pan‐MAGE; M3H67) and New York esophageal squamous cell carcinoma (NY‐ESO‐1; E978) were detected immunohistochemically (IHC) and correlated with clinical data. Results: Expression of NY‐ESO‐1 was found in 48 of 84 patients (57.1%) and of pan‐MAGE in 28 of 84 patients (31.2%). Median overall survival (OS) in NY‐ESO‐1 positive versus negative patients was 130.8 and 282.0 months ( p = .223), respectively. OS in pan‐MAGE positive versus negative patients was 105.3 and 190.5 months, respectively ( p = .096). Patients expressing both NY‐ESO‐1 and pan‐MAGE simultaneously had significantly reduced OS with a median of 90.5 months compared with 282.0 months in negative patients ( p = .047). Conclusion: A significant fraction of patients with ACC show expression of the CTAs NY‐ESO‐1 and/or pan‐MAGE with promising immunotherapeutic implications. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1008–1016, 2016